1995
DOI: 10.1007/bf01690876
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella among women of childbearing age in Switzerland

Abstract: A seroepidemiological study was carried out in Switzerland to define the population susceptible to rubella among women of childbearing age. IgG antibodies to rubella virus were determined in 9,046 women giving birth between 1 August 1990 and 30 September 1991 in 23 of 26 Swiss cantons. These sera represented 10-20% of the yearly total number of births in each Swiss canton. Anti-rubella IgG was measured by an automated enzyme-linked fluorescent assay for use with a commercial system (Vidas Rub IgG, bio-Mérieux,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Regional differences, as those found in our study were observed also in other countries for both rubella [22,28] and measles [31], which may be a result of different epidemiological patterns and different vaccination coverage rates [32] among regions. Lower rubella incidence of seropositivity in rural females, probably due to a lower population density, was observed in different studies in different parts of the world [25,28,33].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regional differences, as those found in our study were observed also in other countries for both rubella [22,28] and measles [31], which may be a result of different epidemiological patterns and different vaccination coverage rates [32] among regions. Lower rubella incidence of seropositivity in rural females, probably due to a lower population density, was observed in different studies in different parts of the world [25,28,33].…”
Section: Discussionsupporting
confidence: 79%
“…The overall seropositivity rates found in our study were in agreement with the results of other previous rubella seroprevalence studies carried out in some major cities of Argentina [13][14][15][16][17][18][19], and suggest that 90 % of women have rubella infection before 15 years of age. Although increasing age has been associated with an increased percentage of rubella seropositivity in other studies [20,21], no significant increase with age was found in a seroprevalence study among WCBA in Switzerland [22] and among pregnant Turkish women [23]. The lower measles seroprevalence levels found in women <30 years old may reflect increased susceptibility in cohorts born after the introduction of vaccination in the 1970s with insufficient vaccination coverage.…”
Section: Discussionmentioning
confidence: 76%
“…The best way to prevent rubella and CRS is vaccination, which has been applied all over the world. [12][13][14][15][16][17][18][19] To eradicate rubella, the Taiwanese government initiated a nationwide immunization program in 1986 to have all third-grade junior high school girl students (about 14-15 years old) receive rubella vaccinations (the school program). Since then, 5 serosurveys have been conducted, 7,[20][21][22][23] but none was able to evaluate long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian Zufferey J dkk 16 di Swiss tahun 1995 menyatakan prevalensi seropositif antibodi anti-rubela pada perempuan usia subur sebesar 94,3%. Imunisasi MMR di Swiss dilakukan pada usia 5-7 tahun atau pada usia 12-15 tahun pada anak yang belum pernah mendapat imunisasi MMR sebelumnya.…”
Section: Pembahasanunclassified
“…Hasil prevalensi pada penelitian ini juga lebih rendah dibandingkan dengan penelitian-penelitian di berbagai negara lainnya pada kelompok usia yang hampir sama. 4,5,[14][15][16][17][18]20,[23][24][25] Penelitian multisenter yang dilakukan oleh Jarour N dkk 23 di Yordania tahun 2007, tidak terdapat perbedaan prevalensi antara perempuan usia subur yang tinggal di perkotaan dengan yang tinggal di daerah pedesaan. Belum ada data prevalensi di daerah lain di Indonesia, tetapi pada tahun 1967 sudah dilaporkan terdapat 2 kasus sindrom rubela kongenital di RS Sutomo Surabaya.…”
Section: Pembahasanunclassified